New Transformation For The Selection Probability Under Positive Correlation Coefficient (Statistics, Optimization & Information Computing, 2025)
In this paper, we suggested a new transformation for the selection a sample with  probability proportional to size measure with replacement under a positive correlation coefficient between the study variable   and the measure of size variable  . The relative efficiency of the proposed estimator has been studied under a super-population model. A numerical investigation into the performance of the estimator has been made.